Experimental Investigation of Heat Transfer with Various Aqueous Mono/Hybrid Nanofluids in a Multi-Channel Heat Exchanger - Robert Plant (MDPI AG, 2021)
The use of nanofluids for heat transfer has been examined in recent years as a potential method for augmentation of heat transfer in different systems. Often, the use of nanoparticles in a working fluid does not disrupt the system in significant ways. As a result of this general improvement of a system’s heat transfer capabilities with relatively few detrimental factors, nanofluids and hybrid nanofluids have become an area of considerable research interest. One subcategory of this research area that has been under consideration is the concentration of each of the nanoparticles, leading to either successful augmentation or hindrance. The focus of the current experimental investigation was to examine the resulting impact on heat transfer performance as a result of each nanofluid implemented in an identical three-channel heat exchanger. This work examined the experimental impacts of 0.5 wt% titania (TiO2), 1 wt% titania, a mixture of 0.5 wt% titania and 0.5% silica, and a 0.5 wt% hybrid nanofluid of titania synthetically modified with copper-based nanostructures (Cu + TiO2). The experimental work examined a range of heat flux densities from 3.85 W cm−2 to 7.51 W cm−2, and varying flow rates. Each of the nanoparticles were suspended in distilled water and then mixed using an ultrasonic water bath. The performances of each nanofluid were determined using the local Nusselt number to evaluate the possible thermal enhancement offered by each nanofluid mixture. While the 0.5 wt% Cu + TiO2 hybrid nanofluid did significantly increase performance, the use of a 0.5 wt% TiO2/SiO2 double nanofluid in a three-channel heat exchanger exhibited the greatest performance enhancement, with an average increase of 37.3% as compared to water.